Neuronal ceroid lipofuscinoses type 7 (CLN7): a case series reporting cross sectional and retrospective clinical data to evaluate validity of standardized tools to assess disease progression, quality of life, and adaptive skills - Saima Kayani; Veronica BordesEdgar; Andrea Lowden; Emily R. Nettesheim; Hamza Dahshi; Souad Messahel; Berge A. Minassian; Benjamin M. Greenberg (Orphanet Journal of Rare Diseases, 2024)
Abstract Background This study evaluated the clinical characteristics of neuronal ceroid lipofuscinosis type 7 or CLN7 disease spectrum to characterize the clinical, electrophysiologic and neuroimaging phenotypes. Methods We performed a single-center cross sectional data collection along with retrospective medical chart review in patients with a genetic diagnosis of CLN7. This study received ethical approval by the University of Texas Southwestern Medical Center Institutional Review Board. A total of 8 patients were included between the ages of 4 to 6 years. All patients had a genetic diagnosis of CLN7 with homozygous or compound heterozygous mutations in the MFSD8 gene. The information collected includes patient demographics, developmental history, neurological events including seizures and neurodevelopmental regression along with further evaluation of brain magnetic resonance imaging and electrophysiological findings. The clinical phenotype is described through cross sectional and retrospective data collection and standardized tools assessing quality of life and functional skills. Results Our findings in this cohort of CLN7 patients indicated that development is initially normal with onset of clinical symptoms as early as two years of age. Language problems were noted prior to or at the onset of seizures in all cases. Gait problems were noted prior to seizure onset in 3 of 8 patients, and at or within 6 months after the onset of seizures in 5 of 8 patients. All patients followed a progressive course of language, motor, and neurocognitive deterioration. Congruent with the medical history, our patients had significantly low scores on adaptive abilities. Natural history data such as this can be used to support future clinical trial designs. Conclusions This study provides a comprehensive description of CLN7 disease, highlighting clinical data alongside standardized neuropsychological assessments, neuroimaging, and electrophysiologic data. It emphasizes the value of importance of standardized tools for understanding disease phenotype and their potential use as endpoints in future clinical trials. The findings established can provide a baseline for developing future prospective natural history studies and potential therapeutic clinical trials.